Recent progress and perspectives of continuous in vivo testing device. (December 2022) - Ming, Tao; Luo, Jinping; Xing, Yu; Cheng, Yan; Liu, Juntao; Sun, Shuai; Kong, Fanli; Xu, Shihong; Dai, Yuchuan; Xie, Jingyu; Jin, Hongyan; Cai, Xinxia
Abstract: Devices for continuous in-vivo testing (CIVT) can detect target substances in real time, thus providing a valuable window into a patient's condition, their response to therapeutics, metabolic activities, and neurotransmitter transmission in the brain. Therefore, CIVT devices have received increased attention because they are expected to greatly assist disease diagnosis and treatment and research on human pathogenesis. However, CIVT has been achieved for only a few markers, and it remains challenging to detect many key markers. Therefore, it is important to summarize the key technologies and methodologies of CIVT, and to examine the direction of future development of CIVT. We review recent progress in the development of CIVT devices, with consideration of the structure of these devices, principles governing continuous detection, and nanomaterials used for electrode modification. This detailed and comprehensive review of CIVT devices serves three purposes: (1) to summarize the advantages and disadvantages of existing devices, (2) to provide a reference for development of CIVT equipment to detect additional important markers, and (3) to discuss future prospects with emphasis on problems that must be overcome for further development of CIVT equipment. This review aims to promote progress in research on CIVT devices and contribute to future innovation in personalized medical treatments. Graphical abstract: Image 1 Highlights: A detailed and comprehensive review of continuous in vivo testing device. The nanomaterials, delicate structures and detection principles of the works are discussed. The achievements and shortcomings of the existing devices are summarized. The problems that should be solved in the further development of the devices and the future prospects are put forward.